2020
DOI: 10.1007/s00420-020-01617-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated exhaustion disorder and associated health-related factors among municipal employees in rural areas of northern Sweden

Abstract: Objective The aims of this study among municipal employees in rural areas of northern Sweden were to assess the prevalence of self-rated exhaustion disorder (s-ED), describe plausible between-group differences in self-reported health-related factors among employees with or without s-ED, and identify health-related factors associated with s-ED. Methods In a cross-sectional study, data were collected from 1093 municipal employees (76.1% women) in two rural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
(59 reference statements)
0
6
0
2
Order By: Relevance
“…In the present study, although all mental symptoms except perceived stress had significant differences between the groups, these symptoms frequently occur in connection with stress. A cross-sectional study [ 43 ] examining health-related factors associated with self-rated exhaustion disorder among public employees in Sweden found that cognitive problems, sleep problems, depressive symptoms, high stress, and stomach problems were associated with self-rated exhaustion disorder. A possible explanation in the present study regarding the nonsignificant difference between the groups concerning stress may be that some individuals did not relate their physical or mental symptoms with stress when seeking care, as they were unaware of the potential connections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, although all mental symptoms except perceived stress had significant differences between the groups, these symptoms frequently occur in connection with stress. A cross-sectional study [ 43 ] examining health-related factors associated with self-rated exhaustion disorder among public employees in Sweden found that cognitive problems, sleep problems, depressive symptoms, high stress, and stomach problems were associated with self-rated exhaustion disorder. A possible explanation in the present study regarding the nonsignificant difference between the groups concerning stress may be that some individuals did not relate their physical or mental symptoms with stress when seeking care, as they were unaware of the potential connections.…”
Section: Discussionmentioning
confidence: 99%
“…It showed eleven factors that predicted sick leave, and one of these was poor self-rated physical health. Poor SRH is also a health-related factor associated with self-rated exhaustion disorder, which, in turn, increases the risk of long-term sick leave [ 43 ]. Results from a large Swedish longitudinal study [ 57 ] displayed in a similar way that self-rated health had significant associations with sick leave and disability pension.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for ED are met if respondents experience exhaustion, can identify a stressor, experience at least four related symptoms and are functionally impaired. The s-ED has shown good construct validity [17,22,24,75].…”
Section: Methodsmentioning
confidence: 99%
“…Res. Public Health 2021, 18, 8657 2 of 11 23% [10,[18][19][20][21][22][23], and ED is associated with reduced work ability and sickness absences [24]. Individuals fulfil the diagnostic criteria for ED if they have experienced physical and mental symptoms of fatigue for at least 2 weeks and if the symptoms can be attributed to an identifiable stressor that has been present for at least 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…(2022) [ 1 ] n = 282 OFER ( α = 0,85) Chronische Fatigue (CF) und Erschöpfung werden hier synonym verwendet; CF/Erschöpfung wird oft als ein langwieriger Zustand betrachtet und beinhaltet körperliche, mentale und emotionale Elemente, inklusive anhaltender Müdigkeit, bei der die Genesung nie vollständig eintreten kann Asplund et al. (2020) [ 2 ] n = 1093 s‑ED PSS ( α = 0,74–0,91) Erschöpfung ist durch Energiemangel, kognitive Probleme, Schlafstörungen, depressive Symptome, einen hohen Stresslevel, Magen-Darm-Beschwerden und schlechte selbstberichtete Gesundheit gekennzeichnet Bauer et al. (2020) [ 4 ] n = 24 Während bei Fatigue die physiologische Leistungsfähigkeit nur mit höherer Anstrengung aufrechterhalten werden kann, zwingt Erschöpfung den Körper, auf weitere physiologische Aktivitäten mit gleicher Intensität zu verzichten Broddadóttir et al.…”
Section: Methodikunclassified